2017
DOI: 10.1051/epjconf/201714003076
|View full text |Cite
|
Sign up to set email alerts
|

Arching in three-dimensional clogging

Abstract: Abstract. Arching in dry granular material is a long established concept, however it remains still an open question how three-dimensional orifices clog. We investigate by means of numerical simulations and experimental data how the outflow creates a blocked configuration of particles. We define the concave surface of the clogged dome by two independent methods (geometric and density based). The average shape of the cupola for spheres is almost a hemisphere but individual samples have large holes in the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Mine productivity can be increased by reducing re-work and unplanned rock handling associated with underbreak since reduced recovery drilling improves output by reducing production delays and decreasing the overall cost per tonne. Analytical equations and numerical and physical experiments have found that as few as five or six particles can cause arching (Török et al 2017), e.g. model and experimental results in Figure 3.…”
Section: Figure 1 Underground Mine Design Methods and Their Blast Desmentioning
confidence: 99%
“…Mine productivity can be increased by reducing re-work and unplanned rock handling associated with underbreak since reduced recovery drilling improves output by reducing production delays and decreasing the overall cost per tonne. Analytical equations and numerical and physical experiments have found that as few as five or six particles can cause arching (Török et al 2017), e.g. model and experimental results in Figure 3.…”
Section: Figure 1 Underground Mine Design Methods and Their Blast Desmentioning
confidence: 99%
“…These transitions also occur when particles are driven through confined geometries and clog [Zuriguel, 2014;Thomas and Durian, 2015] or disordered landscapes, where obstacles inhibit movement by pinning particles that would otherwise be mobile [Péter et al, 2018;Reichhardt and Olson Reichhardt, 2017]. Granular materials fall within the jamming paradigm [Majmudar et al, 2007] and clogging behavior is observed in dense flows of elongated grains [Börzsönyi et al, 2016;Török et al, 2017]. Logjams have been explicitly citepd as macroscopic manifestations of granular phenomenology [Börzsönyi and Stannarius, 2013] and invoked as an inspiration in the assembly of nanomaterials [Whang et al, 2003;Yang, 2003].…”
Section: Clogging and Jammingmentioning
confidence: 99%
“…Few experiments of non-spherical shapes [19,[26][27][28] demonstrated that many features of the discharge can be compared to those of spheres when an effective particle radius is introduced. Examples of numerical simulations of silo discharge of non-spherical particles with multisphere-DEM include rods [29] and mixtures of spherical and rodlike grains [30].…”
Section: Introductionmentioning
confidence: 99%
“…The detailed structure and stability of clogs of hard grains has been investigated [10,15,[36][37][38][39][40][41][42][43]. For 3D systems, a few results on clogging structures were obtained using X-ray imaging [26,29].…”
Section: Introductionmentioning
confidence: 99%